Influencia del AIA, AG3 y Kinetina en el color, forma y tamaño de los protocormos de Comparettia falcata (Orchidaceae) durante su germinación bajo condiciones in vitro - Pedroza Manrique, Jaime; Fernández Lizarazo, Christian; Suárez, Silvia Angélica (Revista Científica, 2007)
Comparettia falcata varíes hormonal requirements throughout its germinative process under in vitro conditions cultivated in the basal medium Murashige and Skoog (1962) enriched with the following growth regulators: 3-indoleacetic acid (ATA), 6-furfurylaminopurine (Kinetin) and gibberellic acid (AG3). 1 mg. and 3 mg. of AJA stimulate the protocorms increase and the initiation of the root system; moreover, does not avoid the progressive loss of the photosynthetic pigment.1 and 3 mg. L-' de Kinetina avoids the accelerated loss of the photosynthetic pigment, although it represses the cellular extension proportionally to the increase of its concentration. 3 and 5 mg. L - ' of GA3 more consistently avoids the accelerated loss of the photosynthetic pigment than the Kinetina, and stimulates so much the increase of size of the embryos, like the initiation of root system. In addition, the existence of a synergism between the IAA and the GA 3 as far as the cellular extension was demonstrated.